Regenerated cellulose fiber solar cell. (13th February 2017) - Ebner, Michael; Schennach, Robert; Chien, Huei-Ting; Mayrhofer, Claudia; Zankel, Armin; Friedel, Bettina
Abstract: Wearable electronics and smart textiles are growing fields in the cause to integrate modern communication and computing tools into clothing instead of carrying around smart phones and tablets. Naturally, this also requires power sources to be integrated in textiles. In this paper, a proof-of-concept is presented in the form of a photovoltaic cell based on a commercially available viscose fiber. This was realized using a silver nanowire network around the viscose fiber to establish electrical contact and a photoactive coating using the standard workhorse among organic thin film solar cells, a blend of poly(3-hexylthiophene) and phenyl-C61 -butyric acid methyl ester. The structure and performance of single fiber devices demonstrate their feasibility and functionality. The applied materials and methods are compatible with solution processing, and therefore qualify for potential roll-to-roll large-scale production.